Oxford EAP - De Chazal, Edward (Oxford University Press, 2012)
Oxford EAP develops the essential skills and academic language for learners who are preparing to study in English at university level, from foundation courses to postgraduate research. With authentic content from Oxford textbooks and videos of lecture extracts, Oxford EAP is an ideal course for learners from a wide range of disciplines. Its clear structure and user-friendly approach make it an ideal resource for experienced EAP tutors as well as teachers who are starting out in the field